The Influence of Organizational Climate on Business Excellence in Organizations (Journal of Universal Excellence, 2026)
Research Question (RQ): How does organizational climate influence business excellence in organizations?Purpose: The purpose of the research is to understand what organizational climate is and what impact it has on business excellence in organizations. The aim of this article is to find out how the EFQM 2020 model can be used to improve organizational climate.Method: We examined the scientific and professional literature and analyzed the data obtained through the study.Results: A positive organizational climate is crucial for the success of employees and the organization, it requires alignment between management and employees, alignment of all employees to organizational values, collaboration and continuous change and improvement of different dimensions of organizational climate such as attitudes towards quality, innovation, employee motivation, communication and career development.Organization: A positive organizational climate has a significant impact on managers and the organization by fostering high employee motivation and satisfaction and effective cooperation between management and employees, leading to better results and operational excellence. Managers need to align themselves with the values of the organization, create open communication and encourage innovation and career development, which in turn contributes to better leadership and overall organizational performance.Society: This research aims to highlight the importance of creating a positive organizational climate that influences business excellence in organizations. This business excellence in organization also has an impact on attitudes towards quality of work and life in general, as work and private life are intertwined.Originality: The research was based on the third criterion of the EFQM 2020 model, Stakeholder Engagement, with a focus on employees.Limitations/Future Research: In the research we were limited to the review and analysis of the references we selected.
Keywords: organizational climate; business excellence; the EFQM 2020 model